IMPLEMENTASI KAJIAN BIBLIKAL UNGKAPAN BERBAHAGIALAH ORANG YANG BERTAHAN DALAM PENCOBAAN BERDASARKAN YAKOBUS 1:12-15 - Manase Gulo (Manna Rafflesia, 2017)
This letter of James is shown to the twelve tribes in the overseas, those who are being tossed around related to the socioeconomic level faced by the church, namely the problem between the rich and the poor. So this letter was written before the year 62 AD. In this article we write about the implementation of the blessed expression of those who endure trials in James 1: 12-15. The background is where James says that those who are happy are those who endure trials. In this context it talks about how people's attitudes in the face of temptation, in this case James appealed to the twelve tribes that are overseas so that they endure trials, love God more, persevere in their faith, and are always faithful to God when facing trials. Real happiness is that people are blessed by God, but the problem is only limited to understanding but when confronted with a problem, trials, and lack of needs to be unhappy, less grateful for what is experienced. Therefore this article reminds believers of the true principle of happiness.